Rancang Bangun Sistem Pelacak Posisi Human Indoor Location menggunakan ESP-Now - Rachmawan, Ega Adi; Lilik Subiyanto; Adianto; Mat Syaiin; Aulia Rahma Annisa; Mustika Kurnia Mayangsari (Journal of Applied Smart Electrical Network and Systems, 2025)
This research aims to develop an Internet of Things (IoT)-based employee attendance and position tracking system using the ESP-NOW protocol integrated with a web database. This system is designed to automatically record attendance and monitor the position of employees in real-time using the Trilateration method with the Exponential Path Loss model. Data from the ESP32 device is sent to the MySQL database via the MQTT protocol and displayed in an easily accessible website interface. The results show that the system can efficiently recap daily, weekly, and monthly attendance data, as well as display the position history of employees and guests with sufficient accuracy. With the implementation of this system, the efficiency and accuracy of attendance management and employee monitoring at Sutami Hydroelectric Power Plant has increased significantly.